1991
DOI: 10.1177/00220345910700010201
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of the Matrix Glycoproteins-Tenascin and the ED-sequence-containing Form of Cellular Fibronectin—in Human Permanent Teeth and Periodontal Ligament

Abstract: The expression of two matrix glycoproteins, tenascin and cellular fibronectin (cFN), has been studied in fully developed human permanent teeth, periodontal ligament, and alveolar bone, in both frozen and paraffin-processed material. Polyclonal antibodies to tenascin and a monoclonal antibody recognizing the ED sequence specific to at least some forms of cFN were used. Staining for both tenascin and cFN was positive in the dental pulp, odontoblastic layer, cementoblast-pre-cementum zone, and on the periosteal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0
9

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 40 publications
9
63
0
9
Order By: Relevance
“…Tenascin is found during mineralizing matrices of bone [Thesleff et al, 1987] and is mainly concentrated in mineralized and nonmineralized tissues exposed to mechanical stress [Lukinmaa et al, 1991]. We also found tenascin between the calcification and procalcification layers.…”
Section: Discussionsupporting
confidence: 72%
“…Tenascin is found during mineralizing matrices of bone [Thesleff et al, 1987] and is mainly concentrated in mineralized and nonmineralized tissues exposed to mechanical stress [Lukinmaa et al, 1991]. We also found tenascin between the calcification and procalcification layers.…”
Section: Discussionsupporting
confidence: 72%
“…FN and COLL1 are components of the extracellular matrix (ECM) in the PDL (Lukinmaa et al 1991), and are considered markers for fibroblastic cells (Hou and Yaeger 1993). It has been reported that FN increases the proliferation rate of PDL cells (Kapila et al 1998), which led to the suggestion that FN is associated with PDL regeneration, although the functions of FN in the PDL are virtually unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These cells form the inside surface of the tooth and separate it from the cavum pulpae. Tenascin may thus also be associated with secondary dentine elaboration when pulp cells differentiate into odontoblasts in response to physical stimuli [27][28][29][30] .…”
Section: Proteins Involved In the Healing Process Tenascinmentioning
confidence: 99%